Insights on persistent airway infection by non-typeable Haemophilus influenzae in chronic obstructive pulmonary disease - Ahearn, Christian P. (Pathog Dis, 2017)
Non-typeable Haemophilus influenzae (NTHi) is the most common bacterial cause of infection of the lower airways in adults with chronic obstructive pulmonary disease (COPD). Infection of the COPD airways causes acute exacerbations, resulting in substantial morbidity and mortality. NTHi has evolved multiple mechanisms to establish infection in the hostile environment of the COPD airways, allowing the pathogen to persist in the airways for months to years. Persistent infection of the COPD airways contributes to chronic airway inflammation that increases symptoms and accelerates the progressive loss of pulmonary function, which is a hallmark of the disease. Persistence mechanisms of NTHi include the expression of multiple redundant adhesins that mediate binding to host cellular and extracellular matrix components. NTHi evades host immune recognition and clearance by invading host epithelial cells, forming biofilms, altering gene expression and displaying surface antigenic variation. NTHi also binds host serum factors that confer serum resistance. Here we discuss the burden of COPD and the role of NTHi infections in the course of the disease. We provide an overview of NTHi mechanisms of persistence that allow the pathogen to establish a niche in the hostile COPD airways.